APPLICATION OF PROJECT-BASED LEARNING TO IMPROVE STUDENTS' CREATIVE THINKING ABILITY IN REAL ANALYSIS COURSES - Susi Herawati; Puspa Amelia; Listy Vermana (Prima: Jurnal Pendidikan Matematika, 2023)
Based on the preliminary research in the Real Analysis material, especially those related to limits, it was found that 83.37% of students had moderate and low mathematical reasoning abilities. This condition shows that students are not able to solve problems, because students' creative abilities are low. Developing of student’s creative abilities can be done through Project-Based Learning. This study aims to improve students' creative thinking skills through Project-Based Learning. The approach used in this research is descriptive qualitative. Data analysis is in the form of valid project sheets, practical creative thinking skills using indicators of Fluency, Flexibility, and Novelty. Data was analyzed  with the normalized gain score formula. The results showed that of 12 students who took the Real Analysis course, 75% of students' thinking skills were low, and 25% were moderate. When compared with the conditions before learning for the three indicators 1.25, 1.13, and 0 with after learning there was an increase of 2.17, 2.17 and 0.5.Keywords: Project-Based Learning, creative thinking